Longer-term mortality following SARS-CoV-2 infection in people with severe mental illness: retrospective case-matched study. Issue 6 (2nd November 2021) - Chen, Shanquan; Fernandez-Egea, Emilio; Jones, Peter B.; Lewis, Jonathan R.; Cardinal, Rudolf N.
Summary: Persisting symptoms and dysfunction after SARS-CoV-2 infection have frequently been observed. However, information on the aftermath of COVID-19 is inadequate. We followed up people with severe mental illness (SMI) infected with SARS-CoV-2, and evaluated their longer-term mortality, using data from Cambridgeshire and Peterborough NHS Foundation Trust, UK. We examined the time course and duration of mortality risk from the point of diagnosis. After SARS-CoV-2 infection, people with SMI had a substantially higher risk of death (hazard ratio (HR) = 5.16, 95% confidence interval (CI) 1.56–17.03; P = 0.007) during the first 28 days and during the following 28–60 days (HR = 2.96, 95% CI 1.21–7.26; P = 0.018) than those without infection, but after 60 days the additional risk of death was no longer significant (HR = 2.33, 95% CI 0.83–6.53; P = 0.107).